Sentidos dados por profissionais da atenção primária à participação das famílias no processo de cuidado de pessoas com Síndrome de Down - Caliri, Mariana (2015)
This study was developed using a qualitative method to achieve its general objective: understand some of the meanings attributed by Primary Health Care (PHC) professionals to the roles that families would perform, according to themselves, in the health-disease process of people with Down Syndrome (DS). For that end, an interview corpus that had already been analyzed for other specific objectives was used. A new reading of this corpus confirmed the relevance of the family theme for the interviewees. For this study, the authors considered the assumption that understanding what the professionals think about the families of DS carriers can help improve care for these patients and their families. The analyzed corpus was composed of 16 semi-structured interviews with open-ended questions that were applied to Family Health Strategy professionals of the city of São Carlos, state of São Paulo. The discourse content analysis technique was used while trying to identify, in addition to the themes and subthemes in the interviews, possible representations and experiences of the interviewees on the subject. The identified subthemes were grouped into three thematic categories, with a total of 15 subthemes. The results of this study, which addressed a “micro” context, make it possible to glimpse a “macro” reality, which is possibly experienced by PHC professionals in Brazil in general. The professionals attribute roles and responsibilities to the families that do not seem to be fully shared by the Family Health Units. The professionals perceive many aspects of the families, pointing to some of their needs, the roles that the families perform in their perception and other aspects that influence the care offered by the families. Such perceptions contribute to a critical reflection regarding the practices of healthcare services. They acknowledge weak points and potentialities in family participation. The data obtained suggests that it is important to conduct further research with PHC professionals that are focused on the type of practice that is performed with the families of people with DS, especially in a context where it is possible glimpse changes resulting from the implementation of the National Policy of Comprehensive Care in Clinical Genetics.